Dieback and decline of wild almond (Amygdalus scoparia Spach) in the Harat protected forest of Yazd Province, Iran. Issue 5 (7th July 2019) - Mirabdollahi Shamsi, Morteza; Akbarinia, Moslem; Mirabolfathy, Mansoureh; Manzari, Shahab; Ahmadikhah, Asadollah
Abstract: Wild almond ( Amygdalus scoparia ) is a dominant shrub species in mountain forests of the Irano‐Turanian region. Dieback and decline symptoms of wild almond shrubs were first observed in Harat protected forest (Yazd, Iran) in the autumn of 2014. Since then, the incidence and severity of the disease have increased. To study the aetiology and estimate losses from the disease, field studies were conducted in 2016 and 2017. For this purpose, eight stands were selected, in which 24%–99% of the trees were wild almond in their species composition. In total, 50 cankers and 50 infected twigs of wild almond shrubs were collected. Fungal isolates were identified based on morphological and cultural characteristics, as well as sequence data of ITS1 + 5.8S + ITS2 rDNA. Pathogenicity of fungi was checked on detached shoots and evaluated after 40 days by measuring the discoloured lesion length at the inoculation site. Among 681 wild almond shrubs checked, 84.44% showed decline symptoms with different severities; only 15.56% did not show observable disease symptoms. The most frequent colonizers of infected tissues taken from cankers were Wilsonomyces carpophilus (56%), Thyrostroma cornicola (40%) and Collophorina paarla (30%). Infected twigs were extensively colonized by W. carpophilus (36%), Th. cornicola (24%) and Ulocladium consortiale (24%). Other species, such as Endoconidioma populi, Microsphaeropsis olivacea, Trichoderma asperellum, Paecilomyces formosus, Saccothecium rubi, Preussia sp . and Chaetomium globosum, had lower isolation frequencies. W. carpophilus, Th. cornicola, C. paarla and U. consortiale were found as pathogens on detached wild almond shoots. Based on the frequency of the isolates and the pathogenicity tests, four fungi, such as W. carpophilus, Th. cornicola, C. paarla and U. consortiale, are considered serious contributing agents playing a significant role in the dieback and decline of wild almond. All isolated species are reported for the first time on the wild almond shrubs of the world.